Transaction formalism protocol tool in infrastructure management. Issue 2 (3rd April 2017) - Zeb, Jehan; Froese, Thomas
Abstract : Purpose: The purpose of this paper is to develop an eight-step procedure – transaction formalism protocol (TFP) – in the area of infrastructure management. The proposed TFP is developed from two perspectives: TFP Specification (conceptual) and TFP Tool (application). This paper introduces the TFP Specification and discusses the TFP Tool in detail. Design/methodology/approach: To develop the proposed TFP Tool, a five-step methodology was used: identify and select existing standards, benchmark standards, link and build on these standards, develop the proposed TFP Tool and validate the protocol. Findings: The TFP Specification defines each step as a function for which inputs, controls, mechanisms, tools/techniques and outputs are specified. The TFP Tool comprises a set of forms and guidance that the transaction development personnel, including transaction analysts, transaction designers, software developers, process modellers and industry experts, will use to define transactions in infrastructure management domain. Practical implications: The proposed TFP Tool enables transaction development personnel to define transactions effectively and efficiently for information and communication technology (ICT)-based solutions through defining information in a structured, consistent and easy way. Originality/value: The TFP Tool was built on existing standards incorporating their shortcomings, including lack of a step-by-step procedure to help guide the personnel what to do next, lack of transaction monitoring and improvement steps and lack of standardised forms to collect information in a prescribed format for implementation in ICT-based collaboration systems. The proposed Tool was evaluated and found to be feasible, usable and useful.